Enhancing active citizenship: Developing assessment tools for digital literacy and critical thinking in Indonesian Civics Education - Tirza, Juliana; Tambunan, Aripin; Parwati, Ni Nyoman; Cendana, Wiputra (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2025)
This study aims to develop instruments to measure digital literacy and critical thinking skills within the Civics Education course, addressing the challenge of assessing these essential competencies in the context of modern education. As digital literacy and critical thinking become increasingly crucial for active citizenship, there is a lack of comprehensive and reliable tools to evaluate these skills effectively. The research employs a development method using the 4D model, consisting of four phases: Define, Design, Develop, and Disseminate. In the Define phase, the competencies to be assessed were clearly identified. In the Design phase, the instruments were crafted based on specific indicators of digital literacy and critical thinking. The Develop phase involved testing the reliability and validity of the instruments, while the Disseminate phase prepared the instruments for broader use. The critical thinking instrument was found to have excellent internal consistency, with a Cronbach’s Alpha of 0.908. However, certain items exhibited low item-total correlations, indicating that revisions were necessary. This study contributes to filling the gap in Civics Education by providing a reliable and valid tool for evaluating digital literacy and critical thinking, ultimately supporting the enhancement of students' competencies in these crucial areas for active and informed citizenship.